Met hart en ziel. Socioloog én katholiek: Bevooroordeelde biografische notities* - Thung, Mady A. (Religie & Samenleving, 2022)
Author, Mady Thung, reflects on work and life of her husband Bert Laeyendecker. Laeyendecker was for a long time a leading sociologist in the Netherlands. Not only was he productive in the field of general sociology and sociology of religion, but also in broader subjects such as: modernity, modern culture, science and technology. Furthermore he was active in scientific associations, editorial boards and assessment committees. Because of this broad range of interest, after having described the first stages of his life and his active involvement in critical movements aiming at renewal of the Roman Catholic Church and his work as a professor in general sociology, she concentrates on his research projects dated from the period when they both participated in the work of the Multidisciplinair Centrum voor Kerk en Samenleving (the Multidisciplinary Center for Church and Society). Central themes of research, resulting in many publications, were (among others) critical analyses of the Western culture, and the concept of progress. Next to that Laeyendecker also published about the (mostly inadequate) reactions of the churches in the Netherlands (in particular the Roman Catholic Church) on changes in society after World War II and new religious consciousness. Although Laeyendecker noted that the Christian tradition has lost significant credibility, especially in its presentday rigid Roman Catholic form, the historical origin of that tradition remained important to him. *Oorspronkelijk verschenen in de vriendenbundel Homo Prudens. Religie, cultuur en wetenschap in de moderne samenleving. Redactie André Köbben, Karel Dobbelaere, Joep de Hart en Lambert van Gelder, Leende 2000, 210-225.